Nursing interventions for improving quality of life among patients with coronary heart disease after percutaneous coronary intervention: A scoping review - Firman Sugiharto; Aan Nuraeni; Yanny Trisyani; Azalia Melati Putri; Nuraulia Aghnia Armansyah (Faculty of Nursing Universitas Padjadjaran, 2024)
Background: Percutaneous coronary intervention (PCI) aims to improve the quality of life (QoL) for coronary heart disease (CHD) patients, but many patients still have poor QoL. The impact of poor QoL causes long-lasting feelings of frustration, anxiety, fear, and worry that make a person give up or lose enthusiasm for the future. Objective: This study aimed to describe nursing interventions to improve the QoL of CHD patients after PCI. Methods: This research used the scoping review method by including all full-text primary studies written in English and published between 2013 to 2023 from three databases, EBSCO-host, PubMed, and Scopus, and one e-resource, Sage Journals. The keywords used were “coronary artery disease OR myocardial infarction OR cardiovascular disease AND quality of life AND percutaneous coronary intervention OR PCI OR Angioplasty AND Nursing care OR nursing intervention.” Results: A total of eight articles discussed nursing interventions to improve the QoL among CHD patients after PCI. There are two categories of interventions that nurses can carry out: hospital-based (inpatient or outpatient) rehabilitation and cardiac tele-rehabilitation. Conclusions: Hospital-based (inpatient or outpatient) rehabilitation and tele-rehabilitation interventions potentially improve post-PCI patients’ QoL, psychological well-being, cardiovascular capacity, social support, and adherence to CHD rehabilitation program. Standardized intervention guidelines need to be created in the future for each outcome of interest based on evidence-based findings so that specific interventions to improve the quality of life of CHD patients can be applied directly in daily practice.